Leading Latino Talent to Champion Innovation - McLaughlin, Greg (Business Expert Press, 2014)
Ebook from IG Library ; This book is a study on how to unlock the innovative potential of the US Latino workforce. It goes beyond diversity by looking into how this emerging segment of the workforce views, accepts, and embraces innovation.